Self‐care in coronary heart disease patient and caregiver dyads (HEARTS‐IN‐DYADS)—Protocol of a multicenter longitudinal study. Issue 1 (20th December 2022) - Simonelli, Niccolò; Bolgeo, Tatiana; Iovino, Paolo; Di Matteo, Roberta; Maconi, Antonio; Vellone, Ercole
Abstract: Self‐care performed by patients and the caregiver contribution to this self‐care are essential for improving cardiovascular outcomes; however, so far, no studies have sufficiently investigated this field in Italy. This paper describes a research protocol of a multi‐center longitudinal study designed to investigate the self‐care of patients affected by coronary heart disease (CHD), the caregiver's contribution to this self‐care, the predictors of patient and caregiver self‐care, the mediating role of self‐efficacy, and the self‐care outcomes. Data collection will be performed across seven Italian inpatient settings at baseline and 3 and 6 months from enrollment. Multilevel modeling and actor partner interdependence models will be implemented on a sample of 330 patient–caregiver dyads to adjust for the interdependence of measurements. The study received approval from an ethics committee in Italy and was financed in January 2021 by a grant from the Solidal Foundation in Alessandria. This research will advance the knowledge about the self‐care process in CHD. The results will guide research and clinical practice by identifying variables sensitive to educational interventions.